The macroeconomics of targeting: the case of an enduring epidemic - Bell, Clive; Gersbach, Hans (Discussion paper series, 2006)
What is the right balance among policy interventions in order to ensure economic growth over the long run when an epidemic causes heavy mortality among young adults? We argue that, in general, policies to combat the disease and promote education must be concentrated, in certain ways, on some subgroups of society, at first to the partial exclusion of others. This concentration involves what we term the macroeconomics of targeting. The central comparison is then between programs under which supported families enjoy the benefits of spending on health and education simultaneously (DT), and those under which the benefits in these two domains are sequenced (ST). When levels of human capital are uniformly low at the outbreak, DT is superior to ST if the subsequent mortality rate exceeds some threshold value. Outside aid makes DT more attractive; but DT restricts support to fewer families initially and so increases inequality.
Keywords: Arbeitspapier; Graue Literatur